1990
DOI: 10.1111/j.1748-5827.1990.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and post prandial hyperglycaemia in normal and diabetic dogs

Abstract: Blood glucose responses to three different diets were measured in six normal dogs and in five diabetic dogs stabilised on insulin replacement therapy. In all animals a control canned diet was compared with the same diet containing 20 g wheat bran, and with the same diet containing 20 g guar granules. Reductions in hyper‐glycaemia were demonstrated for 240 minutes following the test meal containing guar in comparison with the control diet in all but one dog, and moderate reductions were demonstrated following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
(1 reference statement)
0
24
0
3
Order By: Relevance
“…The lack of rapid increase in plasma glucose and insulin shortly after feeding in Experiment 1 and to a lesser extent in Experiment 2 was in line with the pattern reported in dogs by some authors (G orya et al 1981; N omura et al 1985). By contrast, B laxter et al (1990) reported reductions in hyperglycaemia for 240 min following a canned test meal containing 20 g guar gum in Beagle dogs. In that study, the concentration of guar gum was approximately 12% in dry matter, which is higher than the concentration used in these experiments.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The lack of rapid increase in plasma glucose and insulin shortly after feeding in Experiment 1 and to a lesser extent in Experiment 2 was in line with the pattern reported in dogs by some authors (G orya et al 1981; N omura et al 1985). By contrast, B laxter et al (1990) reported reductions in hyperglycaemia for 240 min following a canned test meal containing 20 g guar gum in Beagle dogs. In that study, the concentration of guar gum was approximately 12% in dry matter, which is higher than the concentration used in these experiments.…”
Section: Discussionmentioning
confidence: 89%
“…Although dietary fibres (DF) are not considered as essential nutrients, they are nevertheless beneficial to the health (L eibetseder 1982) and are incorporated at a low rate of 1–5% dry matter in most dog foods. They are also used at higher rate, up to 20% dry matter as an aid in the treatment of patients with obesity, diabetes mellitus, gastrointestinal diseases or hyperlipidaemia (B laxter et al 1990; D imski and B uffington 1991; N elson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in diabetic dogs indicate that high‐fibre diets might be associated with improved glycaemic control (Blaxter and others 1990, Nelson and others 1991, Graham and others 1994, Nelson and others 1998, Kimmel and others 2000, Graham and others 2002). However, these studies have compared high‐fibre with low‐fibre diets without including comparison with a typical diet formulated for canine adult maintenance with moderate‐fibre content.…”
Section: Introductionmentioning
confidence: 99%
“…Fibres, however, may have effect when supplemented to dogs with diabetes mellitus, in such particular health situation high fibre diets may reduce glucose concentration after the meal, helping the insulin administration in the control of glucose blood concentration (GRAHAM, et al, 2002). In addition, very high soluble fibre inclusion can change glucose meal response of health dogs, as demonstrated after the supplementation of 15 to 20% of guar gum (on DM basis) (BLAXTER et al, 1990). Such high inclusion rate, however, is not practical and induces other problems like soft stools, lower nutrient digestibility, and poor diet acceptance by the animal.…”
Section: Discussionmentioning
confidence: 99%